(untitled) (Journal of Economic Research & Business Administration, 2016)
The problem of inflation has an important place in economic science, and its indicators and socio-economic impacts play an important role in assessing the economic security of the country and the world economy. In the cases of inflation in the modern world the relevance of the problem of essence, root causes and anti-inflationary policy and its characteristics are determined by the necessity of defining main directions. The world economy is currently unstable and the modalities of its work and evaluated in various ways. The Eurozone is on the verge of a new wave of economic recession. China, Russia and a number of countries shows that markets with the emerging economies experiencing a slowdown of growth. The situation is exacerbated by the decline in world prices for oil countries-exporters of oil observed from mid-2015.